Criminal Responsibility For The Perpetrator Of The Crime Of Sexual Abuse Committed By A Child Perpetrator Against A Child Victim Verdict Number : 35/Pid.Sus-Anak/2023/ Pn Mdn - Michael Nainggolan; Jessie; Novida Silaban; Sigar P. Berutu (Warmadewa Press, 2024)
This study examines the criminal responsibility of juvenile offenders involved in sexual abuse cases, focusing on Decision No. 35/Pid.Sus-Anak/2023/PN Mdn. Indonesia's legal framework for child protection is grounded in the 1945 Constitution and laws such as the Child Welfare Law No. 4 of 1979 and the Child Protection Law No. 35 of 2014. These laws aim to ensure children's rights to safety and balanced development, even when they are involved in criminal activities. Using a normative juridical approach, this research analyzes legal materials related to juvenile justice and child protection. The case study involves a juvenile perpetrator convicted of sexual abuse, highlighting the application of restorative justice principles. The research emphasizes that even when children commit crimes, they should receive legal protection that promotes their rehabilitation. In Decision No. 35/Pid.Sus-Anak/2023, the judge sentenced the juvenile offender to formal education and training, reflecting the goal of restorative justice, which prioritizes rehabilitation over punishment. This case illustrates the importance of considering non-juridical factors, such as psychological and social development, in the juvenile justice process. The study concludes that legal protection for children in conflict with the law should aim to foster their development into law-abiding citizens, aligning with the principles of restorative justice.